Genome-wide association study of mammary gland tumors in Maltese dogs - Kim, Keon; Song, Jung Eun; Joo, Jae Beom; Park, Hyeon A; Choi, Chang Hyeon; Je, Chang Yun; Kim, Ock Kyu; Park, Sin Wook; Do, Yoon Jung; Hur, Tai-Young; Park, Sang-Ik; Lee, Chang-Min (Frontiers in Veterinary Science, 2023)
A genome-wide association study (GWAS) is a valuable tool for investigating genetic and phenotypic variation in many diseases. The objective of this study was to identify variations in the genomes of Maltese dogs that are associated with the mammary gland tumor (MGT) phenotype and to assess the association between each biological condition and MGT phenotype in Maltese dogs. DNA was extracted from 22 tumor samples and 11 whole blood samples from dogs with MGTs. Genome-wide single-nucleotide polymorphism (SNP) genotyping was performed, and the top 20 SNPs associated with various conditions and genetic variations were mapped to their corresponding gene locations. The genotyping process successfully identified 173,662 loci, with an overall genotype completion rate of 99.92%. Through the quality control analysis, 46,912 of these SNPs were excluded. Allelic tests were conducted to generate Manhattan plots, which showed several significant SNPs associated with MGT phenotype in intergenic region. The most prominent SNP, located within a region associated with transcription and linked to the malignancy grade of MGT, was identified on chromosome 5 (p=0.00001) though there may be lack of statistical significance. Other SNPs were also found in several genes associated with oncogenesis, including TNFSF18, WDR3, ASIC5, STAR, and IL1RAP. To our knowledge, this is the first GWAS to analyze the genetic predisposition to MGT in Maltese dogs. Despite the limited number of cases, these analyzed data could provide the basis for further research on the genetic predisposition to MGTs in Maltese dogs.